Turkish Version Study of "Parkinson's Disease Quality of Life Questionnaire" (PDQL) - (:unkn) unknown (My University, 2015)
Amaç: Bu çalışma Parkinson hastalığı olan hastaların yaşam kalitesini de- ğerlendirmek için geliştirilen "Parkinson Hastalığı Yaşam Kalitesi Sorgulama Formu'nun (PDQL-TR)" Türkçe kültürel adaptasyonunu, geçerlilik ve gü- venilirliğini araştırmayı amaçlamıştır. Yöntem: İstanbul Üniversitesi İstanbul Tıp Fakültesi, Fiziksel Tıp ve Rehabilitasyon Anabilim Dalı'nın polikliniğine Haziran 2005-Nisan 2008 tarihleri arasında başvuran, Parkinson hastalığı tanısı almış 89 hasta çalışmaya dahil edilmiştir. PDQL'in Türkçe versiyonu (PDQL-TR), "Birleştirilmiş Parkinson Hastalığı Derecelendirme Ölçeği" (UPDRS), "Hoehn & Yahr (H & Y) skalası" temel sonuç ölçüm yöntemleri olarak kullanıdı. Bulgular: PDQL-TR, H&Y ve UPDRS skalaları için hesaplanmış Pearson korelasyon katsayısı -0,36 ve-0,80 arasında değişmekteydi. PDQL-TR sorgulama formunun total ve alt grup skorlarının Cronbach alpha katsayısı 0,80'den yüksekti. Madde toplam puan değeri Pearson korelasyon kat sayı- sı 0,40 (4.soru-toplam skor) ve 0,88 (26. soru-toplam skor) arasında değiş- mekteydi, alt-grup toplam skorlarının korelasyon katsayıları ise 0,81 ile 0,96 arasındaydı. PDQL-TR'nin sınıf içi korelasyon sonuçları 0,75 (emosyonel fonksiyon) ve 0,88 (Parkinson semptomları) aralığında yer alarak, yüksek stabilite göstermiştir. Sonuç: PDQL-TR'nin psikometrik özellikleri memnuniyet vericidir ve sonuçlarımız önceki literatür bulgularıyla uyum göstermektedir. PDQL-TR Parkinson hastalığı olan hastaların sağlıkla ilişkili yaşam kalitelerini ölçmede geçerli ve güvenilir bir sorgulama formudur.

Introduction: This study aimed to evaluate Turkish transcultural adaptation, reliability, and validity of "Parkinson's Disease Quality of Life Questionnaire" (PDQL), which has been developed to assess the quality of life of patients with Parkinson's disease. Methods: Eighty-nine patients who were included in the study were diagnosed with Parkinson's disease. They were presented to the outpatient clinic of the Istanbul Faculty of Medicine, Physical Medicine and Rehabilitation department between July 2005 and April 2008. The Turkish translated version of PDQL (PDQL-TR), "Unified Parkinson's Disease Rating Scale" (UPDRS), and Hoehn & Yahr (HY) were used as the main outcome measures. Results: The calculated Pearson correlation coefficient for PDQL, H&Y, and UPDRS ranged between -0.36 and -0.80. Cronbach's alpha coefficients of the PDQL-TR complete questionnaire and subdomains were higher than 0.80. The absolute value of item-total score correlation coefficients by Pearson fluctuated between 0.40 (question 4-total score) and 0.88 (question 26-total score), whereas the subdomain-total score correlation coefficients ranged between 0.81 and 0.96. PDQL-TR showed high stability according to the ICC results, ranging between 0.75 (Emotional Function) and 0.88 (Parkinsonian Symptoms). Conclusion: The psychometric features of PDQL-TR are satisfactory, and our results are consistent with the previous literature findings. PDQLTR is a valid and reliable tool to measure health-related quality of life in patients with Parkinson's disease.
Parkinson Hastalığı Yaşam Kalitesi Sorgulama Formu (PDQL-TR)"nun Türkçe Versiyon Çalışması
Keywords: Nörolojik Bilimler; Psikiyatri